Differential effects of MEK inhibitors on rat neural stem cell differentiation: Repressive roles of MEK2 in neurogenesis and induction of astrocytogenesis by PD98059. (November 2019) - Lee, Ha-Rim; Lee, Jeewoo; Kim, Hyun-Jung
Graphical abstract: Abstract: Neural stem cells (NSCs) proliferate and differentiate into neurons and glia depending on the culture environment. However, the underlying mechanisms determining the fate of NSCs are not fully understood. Growth factors facilitate NSC proliferation through mitogen-activated protein kinase (MAPK)/extracellular signal–regulated kinase (ERK) kinase (MEK) and MAPK activation, and NSCs differentiate into neurons, astrocytes, or oligodendrocytes when mitogens are withdrawn from the culture media. Here, we aimed to identify the effects and roles of MEK signaling on the determination of NSC fate. MEK inhibitors, U0126, SL327, and PD98059, had differential effects on NSC differentiation. U0126 and SL327, which are known to inhibit MEK1 and MEK2, induced neuronal differentiation, whereas PD98059, which is reported to preferentially inhibit MEK1 at higher concentrations, increased astrocytogenesis. Knockdown of MEK2 using small interfering RNA increased neurogenesis and over-expression of wild type (WT) MEK2 inhibited neurogenesis, suggesting a repressive role of MEK2 in neuronal differentiation. The chemical structure of PD98059 appears to be important for induction of astrocytogenesis because not only PD98059 (2′-amino-3′-methoxyflavone) but also its chemical structural mimetic, 3′-methoxyflavone, enhanced astrocytogenesis. Therefore, in our study, we suggest that MEK inhibitors have distinct functions in determining NSC fate. Inhibition of MEK2 is important for induction of neurogenesis in NSCs. U0126 and SL327 increase neurogenesis through MEK2 inhibition, whereas PD98059 induced astrocytogenesis in NSCs, which is mediated by the chemical structure, particularly the 3′-methoxy group rather than its renowned MEK1 inhibition.